2000
DOI: 10.1073/pnas.200362897
|View full text |Cite
|
Sign up to set email alerts
|

On the tryptophan residue of smooth muscle myosin that responds to binding of nucleotide

Abstract: D iscoveries that on binding MgATP (or MgADP) the intrinsic UV absorbance (1) and fluorescence intensity (2) of myosin changes have enabled the quantitative-albeit empirical-study of myosin ATPase kinetics (3, 4). Earlier studies have attempted to distinguish between various classes of Trp and to determine the nature and identity of the Trp residues, whose fluorescence is most influenced on addition of nucleotide (5, 6). However, it has not been known which tryptophan residue [there are seven for skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…There is now abundant evidence that this signal arises from a conserved tryptophan residue (Dd W501 Malnasi-Csizmadia et al 2000), skeletal W510 (Park & Burghardt 2000) and smooth myosin W512 (Onishi et al 2000;Yengo et al 2000)). By using a single tryptophan construct (i.e.…”
Section: Probes Of Switch 2 Movementsmentioning
confidence: 99%
“…There is now abundant evidence that this signal arises from a conserved tryptophan residue (Dd W501 Malnasi-Csizmadia et al 2000), skeletal W510 (Park & Burghardt 2000) and smooth myosin W512 (Onishi et al 2000;Yengo et al 2000)). By using a single tryptophan construct (i.e.…”
Section: Probes Of Switch 2 Movementsmentioning
confidence: 99%
“…AcNPV͞ELC͞RLC viruses (for essential and regulatory light chains) were prepared (11). Expression and purification of recombinant HMMs were carried out (7,12), except that affinity-purified His-tagged HMMs were further purified by chromatography using a Pharmacia MonoQ column. To remove bound nucleotides from mutant HMMs, the preparation was dialyzed for 2 days against 500 ml of buffer, 0.45 M KCl, 1 mM EDTA, 20 mM Tris⅐HCl (pH 7.5), and 0.5 mM DTT, on ice with four-time buffer changes.…”
Section: Preparation Of Recombinant Heavy Meromyosins (Hmm)mentioning
confidence: 99%
“…Several studies (12,(15)(16)(17) have suggested that Trp-512 (of smooth muscle myosin) is the responsible Trp residue. Crystallographic studies demonstrated that the ATP-induced rotation of the lower piece of 50 kDa, which bears Trp-512 at its tip, can perturb this fluorophore (5).…”
Section: Increase In Trp Fluorescence Of Hmms By Binding Of Atpmentioning
confidence: 99%
See 1 more Smart Citation
“…W506F retains nucleotide sensitive fluorescence enhancement despite significant perturbation of ATPase functionality. W5061(Y499F) also shows a perturbed ATPase functionality common for side-chain modifications in the vicinity of W506 (46,47).…”
Section: Introductionmentioning
confidence: 99%